Association between diet of the vegan population and self-perception of periodontal state in Metropolitan Lima - Reyes-Izquierdo, Alicia (2022)
Introduction: Objective: to determine the association between vegan diet and self-perceived periodontal status in a vegan population of Metropolitan Lima, Peru. Materials and methods: a total of 240 people (120 vegans and 120 non-vegans) were surveyed in this study during the months of August to December 2020 in a virtual way. To evaluate self-perception of periodontal status and oral hygiene habits, the self-report of periodontal disease was used, which is validated with a Cronbach's alpha of 0.77. In addition, other variables such as age, sex, socioeconomic level, educational level, and tobacco consumption were registered. A Poisson regression with robust variance estimator was used both for the association of variables, and prevalence ratios were reported in a crude and adjusted model. The confidence level was 95 % and the significance level was p < 0.05. Results and conclusions: a statistically significant association was found between the appearance of reddish and/or swollen gums (PR = 0.67; 95 % CI: 0.25-0.54) and poor perception of the state of the gums (PR = 0.43; 95 % CI: 0.33-0.56) with the vegan diet. Finally, for the gum bleeding dimension during brushing, no statistically significant differences were observed between vegans and non-vegans.